Digital Saint-Domingue: Playing Haiti in Videogames - Lauro, Sarah Juliet (Archipelagos, 2017)
This article comes out of a longer project looking at digital commemorations of slave rebellion. In this excerpt from that work, the author considers the issues at stake in videogamic representations of colonial Saint Domingue and its denizens, particularly for their depiction of the prehistory of the Haitian Revolution. In two mainstream videogames, both part of the Assassin’s Creed franchise, the history of Saint Domingue, its legacy of slave resistance, and the Haitian Revolution are made into fodder for an interactive entertainment experience that intervenes in and reshapes history in a complex manner. There are several issues at stake, which the author focuses on exclusively in terms of the commodification of Saint Domingue. First, the games place the history of slave revolt into the hands of game players of diverse ancestry, allowing for a redistribution of ownership over narratives of emancipation and empowerment. Second, the games identify themselves as tampering with history, and their mélange of fictional characters and real personages seems to risk rewriting the history of Saint Domingue’s legacy of slave revolt and—by extension—of the Haitian Revolution itself. Given recent events in the United States, and increased attention to strategies of black resistance such as the Black Lives Matter movement, it seems all the more imperative that our depiction of slave revolts in popular culture be handled with care. And yet, the author finds a subversive maneuver visible in the games: the use of untranslated language, especially Haitian Kreyol, may work to preserve and limit the player’s mastery over these histories. This article provides a tour of this complex territory of digital Saint Domingue.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

The Transatlantic Zombie: Slavery, Rebellion, and Living Death - Lauro, Sarah Juliet. (American literatures initiative, 2015)
Our most modern monster and perhaps our most American, the zombie that is so prevalent in popular culture today has its roots in African soul capture mythologies. The Transatlantic Zombie provides a more complete history of the zombie than has ever been told, explaining how the myth's migration to the New World was facilitated by the transatlantic slave trade, and reveals the real-world import of storytelling, reminding us of the power of myths and mythmaking, and the high stakes of appropriation and homage. Beginning with an account of a probable ancestor of the zombie found in the Kongolese and Angolan regions of seventeenth-century Africa and ending with a description of the way, in contemporary culture, new media are used to facilitate zombie-themed events, Sarah Juliet Lauro plots the zombie's cultural significance through Caribbean literature, Haitian folklore, and American literature, film, and the visual arts. The zombie entered US consciousness through the American occupation of Haiti, the site of an eighteenth-century slave rebellion that became a war for independence, thus making the figuration of living death inseparable from its resonances with both slavery and rebellion. Lauro bridges African mythology and US mainstream culture by articulating the ethical complications of the zombie's invocation as a cultural conquest that was rebranded for the American cinema. As The Transatlantic Zombie shows, the zombie is not merely a bogeyman representing the ills of modern society, but a battleground over which a cultural war has been fought between the imperial urge to absorb exotic, threatening elements, and the originary, Afro-disaporic culture's preservation through a strategy of mythic combat
Keywords: 2-Histoire/Historiographie critique; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Zombie theory: a reader - Lauro, Sarah Juliet (University of Minnesota Press, 2017)
Zombies first shuffled across movie screens in 1932 in the low-budget Hollywood film White Zombie and were reimagined as undead flesh-eaters in George A. Romero's The Night of the Living Dead almost four decades later. Today, zombies are omnipresent in global popular culture, from video games and top-rated cable shows in the United States to comic books and other visual art forms to low-budget films from Cuba and the Philippines. The zombie's ability to embody a variety of cultural anxieties--ecological disaster, social and economic collapse, political extremism--has ensured its continued relevance and legibility, and has precipitated an unprecedented deluge of international scholarship. Zombie studies manifested across academic disciplines in the humanities but also beyond, spreading into sociology, economics, computer science, mathematics, and even epidemiology. Zombie Theory collects the best interdisciplinary zombie scholarship from around the world. Essays portray the zombie not as a singular cultural figure or myth but show how the undead represent larger issues: the belief in an afterlife, fears of contagion and technology, the effect of capitalism and commodification, racial exclusion and oppression, dehumanization. As presented here, zombies are not simple metaphors; rather, they emerge as a critical mode for theoretical work. With its diverse disciplinary and methodological approaches, Zombie Theory thinks through what the walking undead reveal about our relationships to the world and to each other.
Keywords: 2-Histoire/Historiographie critique; 2-Étude des représentations; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Kill the Overseer!: the Gamification of Slave Resistance - Lauro, Sarah Juliet. (Forerunners: Ideas First Ser., 2020)
Profiles and problematizes digital games that depict Atlantic slavery and "gamify" slave resistance. In videogames emphasizing plantation labor, the player may choose to commit small acts of resistance like tool-breaking or working slowly. Others dramatically stage the slave's choice to flee enslavement and journey northward, and some depict outright violent revolt against the master and his apparatus. This work questions whether the reduction of a historical enslaved person to a digital commodity in games such as Mission US, Assassin's Creed, and Freedom Cry ought to trouble us as a further commodification of slavery's victims, or whether these interactive experiences offer an empowering commemoration of the history of slave resistance.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé